Avaliação do uso de Zantedeschia aethiopica para o tratamento de águas cinzas proveniente de máquina de lavar roupa - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Water plays a vital role in human existence and a wide array of essential activities. However, the reality of millions of Brazilians lacking access to clean drinking water, coupled with substantial losses in the distribution system, underscores the urgent need for adopting sustainable management strategies for this indispensable resource. Within this context, the reuse of greywater, particularly from washing machines, emerges as a pivotal solution. This study examined the utilization of Zantedeschia aethiopica in a prototype designed to treat greywater originating from washing machines, utilizing gravel as a substrate. Various hydraulic retention times (HRT) - 4, 8, 24, 48, and 72 hours - underwent meticulous evaluation, revealing the efficacy of the wetlands system in maintaining pH and dissolved oxygen values, while significantly reducing turbidity and substantially lowering the biochemical oxygen demand (BOD5/20) by approximately 91.9%. Notably, this index notably surpasses the requirement stipulated by Resolution 430/2011 of CONAMA, which sets a standard of 60% for this parameter. These findings underscore the promising potential of Zantedeschia aethiopica in enhancing the purification process of greywater, demonstrating its positive impact on increasing dissolved oxygen levels and decreasing oxygen demand, both recognized as classical contamination indicators. However, it emphasizes the pressing need for further investigations to validate and delve deeper into these outcomes, meticulously considering the various variables that influence the effectiveness of plant-based treatment.
Keywords: Gestão sustentável; Reutilização de águas cinzas; Eficácia do tratamento; Alagados artificiais; Greywater reuse; Treatment effectiveness; Artificial wetlands; CNPQ::ENGENHARIAS